Proportion and Associated Factors of Nonreassuring Fetal Heart Rate Patterns in Finote Selam Primary Hospital, North West Ethiopia. (21st September 2020) - Kassahun, Eden Asmare; Aweke, Amlaku Mulat; Getu, Almaz Aklilu; Gela, Getahun Belay; Limenih, Simachew Kassa; Mekonnen, Mesafint Ewnetu; Abtie, Tilksew Ayalew
Abstract : Introduction . Nonreassuring fetal heart rate patterns (NRFHRP) suggest fetal conciliation or a deteriorating ability to handle the stress of labor. Nearly half of stillbirths occurring worldwide are due to hypoxia which is primarily manifested by NRFHRP. Hence, this study assessed the proportion and associated factors of NRFHRP in the Finote Selam primary hospital, North West Ethiopia. Methods . An institution-based retrospective cross-sectional study was conducted from March 1 to April 1, 2019, on 364 charts of mothers who gave birth from January 2017 to January 2018 at the Finote Selam primary hospital. A computer-based simple random sampling technique was used to select charts. A secondary data was collected using a structured questionnaire adapted from different literatures. The data was entered and analyzed using Epi Info version 7 and Statistical Package for the Social Sciences (SPSS) version 23.0. Binary logistic regression was executed, and all explanatory variables with p value < 0.2 were entered into multivariable logistic regressions. Multivariable logistic regression was used to control the effect of confounding variables and to identify factors affecting NRFHRP. Odds ratios with 95% confidence intervals were computed, and statistical significance was declared if p < 0.05 . Result . Out of 364 total deliveries, NRFHRP was detected on 55 (15.1%) fetuses, and the commonest NRFHRP detected was bradycardia 44 (80%). Most NRFHRP (38.18%) occurred on the deceleration phase of labor. There was no identified possible cause for NRFHRP on 34.5% of cases. Referral from nearby health institutions [AOR = 2.832 (95% CI 1.457, 5.503)], primigravida [AOR = 2.722 (95% CI 1.377, 5.381)], augmentation of labor [AOR = 3.664 (95% CI 1.782, 7.534)], and meconium-stained amniotic fluid [AOR = 6.491 (95% CI 3.198, 13.173)] were significantly associated with NRFHRP. Conclusion . The proportion of NRFHRP is high. Referral from nearby health institutions, primigravida mothers, augmentation of labor, and meconium-stained amniotic fluid were significantly associated with NRFHRP. Implementing a better referral link and close monitoring during follow-up could minimize NHFHRP.